THE EFFECTIVENESS OF ICE BREAKING FOR STUDENTS’ SPEAKING SKILLS AT SMP IT AL IKHWAN TANJUNG MORAWA ACADEMIC YEAR 2021/2022 - Istiqfarrin Miranto; Ahmad Laut Hasibuan (Sekolah Tinggi Pariwisata Mataram, 2022)
The objective of this research was to find out the effectiveness of Ice Breaking for students’ speaking skills at the eighth-grade s of SMP IT Al Ikhwan Tanjung Morawa Academic Year 2021/2022. The type of research was quantitative research, and it was conducted by using experimental design with two classes, in experimental class consisted of 22 students and control class consisted of 21 students. In technique of collecting data, the researcher conducted pre-test, treatment and post-test by speaking test. The data were analyzed by using t-test formula. The result of the data showed that tobserve (5,80) value was higher than the ttable in which tobserve>ttable (5,80>1,68). The finding showed that the hypothesis was accepted. It can be concluded that there was significant difference score in speaking skill for the students who were taught by ice breaking technique and who were not taught by ice breaking technique. Based on the explanation above, the researcher concluded that ice breaking technique is effective for teaching speaking of the eighth-grade students at SMP IT Al Ikhwan Tanjung Morawa Academic Year 2021/2022.